SPIRITUALITAS DAN KERESAHAN MANUSIA MODERN - Hasan Mud'is (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2016)
In the life of modern society, a man underwent a spiritual downfall. Rationalism, empiricism, and pragmatism have become a significant thought for every man. God, paradise, and hell is no longer a frightening problem because it is considered obsolete and irrational. Man becomes master for himself. Man is driven to think about this worldly life. Because of neglecting spiritual needs, a modern man did not find a peaceful spiritual life. It means there is no balance in himself. Modernism is not able to fulfill spiritual needs of man. It is no surprised if now man makes serious efforts together to fulfill his spiritual needs by filling spiritual emptiness and searching the meaning of life.